Genetic and phenotypic analyses reveal major quantitative loci associated to fruit size and shape traits in a non-flat peach collection (P. persica L. Batsch). (1st November 2021) - Cirilli, Marco; Baccichet, Irina; Chiozzotto, Remo; Silvestri, Cristian; Rossini, Laura; Bassi, Daniele
Abstract: Fruit size and shape are critical agronomical and pomological attributes and prime targets in peach breeding programs. Apart from the flat peach type, a Mendelian trait well-characterized at the genetic level, ample diversity of fruit size and shapes is present across peach germplasms. Nevertheless, knowledge of the underlying genomic loci remains limited. In this work, fruit size and shape were assessed in a collection of non-flat peach accessions and selections, under controlled fruit load conditions. The architecture of these traits was then dissected by combining association and linkage mapping, revealing a major locus on the proximal end of chromosome 6 ( qSHL/Fs6.1 ) explaining a large proportion of phenotypic variability for longitudinal shape and also affecting fruit size. A second major locus for fruit longitudinal shape ( qSHL5.1 ), probably also affecting fruit size, was found co-localizing at locus G, suggesting pleiotropic effects of peach/nectarine traits. An additional QTL for fruit longitudinal shape ( qSHL6.2 ) was identified in the distal end of chromosome 6 in a cross with an ornamental double-flower peach and co-localized with the Di2 locus, controlling flower morphology. Besides assisting breeding activities, knowledge of loci controlling fruit size and shape paves the way for more in-depth studies aimed at the identification of underlying genetic variant(s).